EDUKASI HADIS AKTHAR AHL AN-NĀR AL-NISĀ’ DI MAJELIS MUSLIMATAN DESA KATOL BARAT - Halwiyah, Wiwik; Hasanah, Makrunatul; Ulfa, Latifatul; Sadiyah, Fatichatus (CV. Agrapana Media, 2026)
Cursing and denying the goodness of one's husband are two acts that cause women to become the most numerous inhabitants of hell and are two things that usually occur in married life, so it is necessary to conduct Islamic studies based on the Qur'an and hadith to prevent this. Islamic education is a program held to provide the community with a deep understanding of the hadith that reads Akthar Ahl an-Nār al-Nisā' as an effort to prevent wives from cursing and denying their husbands. The education program, packaged in the form of da'wah, was delivered to the Jama'ah Majelis Muslimatan in the village of Katol Barat, Geger District, Bangkalan Regency, whose members are all married women. This program was carried out using lectures and case studies of community habits related to the material presented. The results of this program provided a deep understanding of behaviors that are usually considered normal, such as cursing, even though it is prohibited in Islam.